Determinants of Utilization of Antenatal Care Services by Pregnant Women at the Berastagi Health Center in Karo District in 2019 - Sibagariang, Eva Ellya; Marlinang I. Silalahi (Akupun Tour Publisher, 2023)
Purpose: One of the risk factors for maternal mortality and morbidity is the undetected danger signs during pregnancy due to irregular ANC visits. The coverage of health services for visits by pregnant women K1 and K4 at the Berastagi Health Center has not reached the target set by the Karo District Health Office. Based on data for the last 3 months at the Berastagi Garden Health Center in 2019, the coverage of ANC services with the target number of pregnant women was 1158 (100%) (K1 and K4), namely in April K1 87 (7.5%) and K4 81 (7.0%), in in May KI 82 (7.1%), K4 80(6.9%), in June K1 80 (6.9%) K4 79 (6.8%). This coverage has not yet reached the minimum district/city health service standards. This study aims to determine whether